Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

First Report of Root Rot Caused by Pythium spiculum Affecting Cork Oaks at Donana Biological Reserve in Spain - De Vita, P.; Serrano, M. S.; Ramo, C.; Aponte, C.; Garcia, L. V.; Belbahri, L.; Sanchez, M. E. (PLANT DISEASE, 2013)
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: Cork oak; Donana Biological Reserve; Pythium spiculum; Spain

Holocene vegetation, fire and climate interactions on the westernmost fringe of the Mediterranean Basin - Morales-Molino, César; García-Antón, Mercedes; Postigo-Mijarra, José M; Morla, Carlos (Quaternary Science Reviews, 2013)
A new palaeoecological sequence from the western Iberian Central Range signiﬁcantly contributes to the knowledge on the Holocene vegetation dynamics in central Iberia. This sequence supports the existence of time-transgressive changes in the vegetation cover during the beginning of the Holocene over these central Iberian mountains, speciﬁcally the replacement of boreal birchepine forests with Mediterranean communities. Anthracological analyses also indicate the replacement of boreal pines (Pinus sylvestris) with Mediterranean ones (Pinus pinaster) during the early Holocene. The observed vegetation changes were generally synchronous with climatic phases previously reconstructed for the western Mediterranean region, and they suggest that the climatic trends were most similar to those recorded in the northern Mediterranean region and central Europe. Several cycles of secondary succession after ﬁre ending with the recovery of mature forest have been identiﬁed, which demonstrates that the vegetation of western Iberia was highly resilient to ﬁre disturbance. However, when the recurrence of ﬁre crossed a certain threshold, the original forests were not able to completely recover and shrublands and grasslands became dominant; this occurred approximately 5800e5400 cal yr BP. Afterwards, heathlands established as the dominant vegetation, which were maintained by frequent and severe wildﬁres most likely associated with human activities in a climatic framework that was less suitable for temperate trees. Finally, our palaeoecological record provides guidelines on how to manage protected areas in Mediterranean mountains of southwestern Europe, especially regarding the conservation and restoration of temperate communities that are threatened there such as birch stands.
Keywords: Betula; charcoal; Fire ecology; Forest management; Heathlands; macrofossils; pollen; Spain

Interspecific differences in tree growth and mortality responses to environmental drivers determine potential species distributional limits in Iberian forests - Benito-Garzón, Marta; Ruíz-Benito, PALOMA; Zavala, Miguel A. (Global Ecology and Biogeography, 2013)
Aim Tree growth may be enhanced by carbon dioxide fertilization unless drought stress becomes too severe, yet the likely increase in tree growth under a warmer climate is still controversial. Tree mortality has increased in some regions, but its multifactorial nature makes the prediction of likely global trends difficult. The aims of this work are: (1) to assess which abiotic, structural and competition factors influence tree growth and tree mortality in mainland Spain, and (2) to evaluate whether these processes would drive species distributions and would improve current niche model predictions. Location Continental Spain. Methods We projected species distributional models by integrating nonparametric tree growth and tree mortality models based on repeated surveys of diameter at breast height and mortality for 40,721 trees distributed in 45,301 plots, which include the 11 most common canopy tree species in continental Spain, as measured in the second and third National Forest Inventories, with a mean lag time of 11 years. Results Tree growth and tree mortality were explained by an assemblage of many factors, among which climate and competition played a key role. The accuracy of models including tree growth and tree mortality in predicting tree habitat suitability was comparable to classical niche models based on species occurrence. Projections under climate change showed for 9 out of 11 species, a likely increase in tree growth that would be counteracted by an increase in tree mortality, suggesting that even if growth rates increase, mortality would limit the species ranges under global warming expectations. Main conclusions Growth and mortality are major determinants of species distributions. Under future climate change expectations, our model suggests that growth may increase for some Iberian species, but even in this case, species ranges at the rear edge would be limited by an increase in mortality rates.
Keywords: climate change; demographic rates; national forest inventory; phenotypic variability; Spain; species distributional models; tree growth; tree mortality

Modelling the nesting-habitat of the Cinereous Vulture Aegypius monachus on a fine scale for conservation purposes - Guerrero-Casado, Jose; Arenas, Rafael; Tortosa, Francisco S. (BIRD STUDY, 2013)
Capsule Nests of Cinereous Vultures were found to be located farther from roads, villages and the edge of large vegetation patches. They preferred large vegetation patches containing extensive Cork Oak cover on steeper slopes and with lower solar radiation. Less than 8% of the study area was predicted to be suitable for nesting.Aims To generate a predictive habitat suitability map for the Cinereous Vulture's nesting-habitat on a fine scale for conservation applications within its breeding range.Methods Habitat features of 43 nest-locations and random points were compared in order to identify nest-habitat selected in the region of the Hornachuelos Natural Park (Spain). A logistic regression approach was used to create habitat models.Results Compared with random points, nests were found to be located farther from roads, villages and patch edges, and in large vegetation patches containing extensive Cork Oak cover on steeper slopes with lower solar radiation. The predictive map revealed that less than 8% of the study area had a greater probability of occupancy than 0.8.Conclusions Most habitats in the study area are unsuitable for nesting suggesting that conservation of the best suitable areas is important. The fine-scale predictive map approach may be valuable in designating conservation priority areas.
APSAPSThe following values have no corresponding Zotero field: pub-location: 4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND publisher: TAYLOR & FRANCIS LTD
Keywords: Capsule nests; Cork oak; habitat modelling; Spain

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Relationship between projected changes in future climatic suitability and demographic and functional traits of forest tree species in Spain - Lloret, F.; Martínez-Vilalta, J.; Serra-Diaz, J. M.; Ninyerola, M. (Climatic Change, 2013)
The response of plant species to future climate conditions is probably dependent on their ecological characteristics, including climatic niche, demographic rates and functional traits. Using forest inventory data from 27 dominant woody species in Spanish forests, we explore the relationships between species characteristics and projected changes in their average climatic suitability (occurrence of suitable climatic conditions for a species in a given territory) obtained by empirical niche-based models, under a business-as-usual climate change scenario (A1, HadCM3, 2001–2100). We hypothesize that most species will suffer a decline in climatic suitability, with a less severe for species (i) currently living in more arid climates or exhibiting a broader current climatic niche; (ii) with higher current growth rates; (iii) with functional traits related to resistance to water deficits. The analysis confirm our hypothesis since apart from a few Mediterranean species, most species decrease their climatic suitability in the region under future climate, characterized by increased aridity. Also, species living in warmer locations or under a wider range of climatic conditions tend to experience less decrease in climatic suitability. As hypothesized, a positive relationship was detected between current relative growth rates and increase in future climatic suitability. Nevertheless, current tree mortality did not correlate with changes in future climatic suitability. In contrast with our hypothesis, functional traits did not show a clear relationship with changes in climate suitability; instead species often presented idiosyncratic responses that, in some cases, could reflect past management. These results suggest that the extrapolation of species performance to future climatic scenarios based on current patterns of dominance is constrained by factors other than species autoecology, particularly human activity.
APSAPSThe following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: climatic niche; demographic rates; funtional traits; future climate; Spain; woody species

Relationship between projected changes in future climatic suitability and demographic and functional traits of forest tree species in Spain - Lloret, F; Martínez-Vilalta, J; Serra-Diaz, J M; Ninyerola, M (Climatic Change, 2013)
The response of plant species to future climate conditions is probably dependent on their ecological characteristics, including climatic niche, demographic rates and functional traits. Using forest inventory data from 27 dominant woody species in Spanish forests, we explore the relationships between species characteristics and projected changes in their average climatic suitability (occurrence of suitable climatic conditions for a species in a given territory) obtained by empirical niche-based models, under a business-as-usual climate change scenario (A1, HadCM3, 2001–2100). We hypothesize that most species will suffer a decline in climatic suitability, with a less severe for species (i) currently living in more arid climates or exhibiting a broader current climatic niche; (ii) with higher current growth rates; (iii) with functional traits related to resistance to water deficits. The analysis confirm our hypothesis since apart from a few Mediterranean species, most species decrease their climatic suitability in the region under future climate, characterized by increased aridity. Also, species living in warmer locations or under a wider range of climatic conditions tend to experience less decrease in climatic suitability. As hypothesized, a positive relationship was detected between current relative growth rates and increase in future climatic suitability. Nevertheless, current tree mortality did not correlate with changes in future climatic suitability. In contrast with our hypothesis, functional traits did not show a clear relationship with changes in climate suitability; instead species often presented idiosyncratic responses that, in some cases, could reflect past management. These results suggest that the extrapolation of species performance to future climatic scenarios based on current patterns of dominance is constrained by factors other than species autoecology, particularly human activity.
APS
Keywords: climatic niche; demographic rates; funtional traits; future climate; Spain; woody species

The Spanish livestock model: A coevolutionary analysis - Ríos-Núñez, Sandra M; Coq-Huelva, Daniel; García-Trujillo, Roberto (Ecological Economics, 2013)
Coevolution is a wide theoretical framework that enables the study of socio-ecological transformations in different contexts and, specifically, in agrarian systems. This article analyses coevolutionary changes in Spanish livestock over the last 50 years, fromthe so-called “traditional” livestock model, in which ecological, social and economic elements co-evolve in closely interconnected relationships, to the currently dominant industrial livestock model, governed by “ecologies at a distance”. Not only meat consumption grew significantly as a consequence of the change in the prevailing livestock production model, Spain also became one of the most important meat producers in the European Union. Simultaneously, dependence on imported cereals and soya increased dramatically. Nevertheless, in spite of the prevalence of industrial logics, extensive livestock farming, that follows hybrid logics incorporating features from both models, still exists in Spain and, particularly, in Andalusia (Southern Spain). This locally based model is characterised by higher environmental standards, as well as its contribution to the preservation of a singular agro-ecosystem(dehesa). However, its long-termtrans- formation and, therefore, the social construction ofmore sustainable local livestock systems,must be understood as a co-evolutionary process in which agency and social selection of innovations are essential elements.
Keywords: Agro-systems; Coevolution; livestock; Socio-ecological systems; Spain

Knowledge of ethnoveterinary medicine in the Province of Granada, Andalusia, Spain. - Benítez, Guillermo; González-Tejero, M. Reyes; Molero-Mesa, Joaquín (Journal of ethnopharmacology, 2012)
This paper constitutes an important contribution to the knowledge of biological resources used in ethnoveterinary practices (EVPs) in southern Europe, a territory with a clear lack of information on the subject. Aim of the study: To catalogue, analyze, and disseminate the knowledge of plant and animal use in eth- noveterinary practices in the province of Granada. Data have been analyzed to highlight the similarities between ethnoveterinary practices and human ethnopharmacology for the same study area. Methodology: Information was gathered through open and semi-structured interviews with local people, mainly elderly shepherds and farmers, in the western part of the province. The primary data have been supplemented with information on EVPs from previous ethnobotanical works for the province. Data were gathered using the same field methods. Results: A total of 88 ethnoveterinary uses are documented for the treatment of 24 animal conditions. Of these, 82 uses involve 60 different plant species. Over three-quarters of these plants are also used for some human conditions in the same study area. Moreover, 6 animal species were catalogued for 6 other ethnoveterinary uses; four of these species were also used for similar conditions in humans. Ritual and health-prevention practices are also discussed. Conclusions: EVPs in southern Spain involve a high number of species and conditions and are strongly linked to folk tradition (i.e. how local people understand certain conditions and their treatment, some- times in a ritual manner). Unfortunately, some evidence of their slow disappearance has been found.
The following values have no corresponding Zotero field: publisher: Elsevier Ireland Ltd accession-num: 22155471
Keywords: Ethnoveterinary; Granada; Spain; Veterinary medicine; Zootherapy

Proteomic analysis of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) pollen. - Valero Galván, José; Valledor, Luis; González Fernandez, Raquel; Navarro Cerrillo, Rafael M; Jorrín-Novo, Jesús V (Journal of proteomics, 2012)
This paper presents an analysis of Holm oak pollen proteome, together with an evaluation of the potentiality that a proteomic approach may have in the provenance variability assessment. Proteins were extracted from pollen of four Holm oak provenances, and they were analyzed by gel-based (1- and 2-DE in combination with MALDI-TOF/TOF) and gel-free (nLC-LTQ Orbitrap MS) approaches. A comparison of 1- and 2-DE protein profiles of the four provenances revealed significant differences, both qualitative and quantitative, in abundance (18 bands and 16 spots, respectively). Multivariate statistical analysis carried out on bands and spots clearly showed distinct associations between provenances, which highlight their geographical origins. A total of 100 spots selected from the 402 spots observed on 2-DE gels were identified by MALDI-TOF/TOF. Moreover, a complementary gel-free shotgun approach was performed by nLC-LTQ Orbitrap MS. The identified proteins were classified according to biological processes, and most proteins in both approaches were related to metabolism and defense/stress processes. The nLC-LTQ Orbitrap MS analysis allowed us the identification of proteins belonging to the cell wall and division, transport and translation categories. Besides providing the first reference map of Holm oak pollen, our results confirm previous studies based on morphological observations and acorn proteomic analysis. Moreover, our data support the valuable use of proteomic techniques as phylogenetic tool in plant studies.
Keywords: Electrophoresis, Gel, Two-Dimensional; Electrophoresis, Gel, Two-Dimensional: methods; Electrophoresis, Polyacrylamide Gel; phylogeny; Plant Proteins; Plant Proteins: analysis; pollen; Pollen: chemistry; Proteome; Proteome: analysis; Proteomics; Proteomics: methods; Quercus; Quercus: genetics; Quercus: metabolism; Spain; Spectrometry, Mass, Matrix-Assisted Laser Desorpti; Two-Dimensional Difference Gel Electrophoresis

Sarcosaprophagous Diptera assemblages in natural habitats in central Spain: spatial and seasonal changes in composition - MARTÍN-VEGA, D; Baz, A (Medical and Veterinary Entomology, 2012)
The composition and spatial distribution of sarcosaprophagous Diptera assemblages were studied using carrion-baited traps along a bioclimatic gradient of natural habitats in central Spain throughout the different seasons during 1 year. Calliphoridae and Muscidae were the most abundant families, accounting for, respectively, 41.9% and 35.1% of all Diptera specimens collected. Other abundant families were Heleomyzidae (8.4%), Sarcophagidae (6.9%) and Piophilidae (5.1%). Fly assemblage compositions differed among bioclimatic levels, with Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) being the dominant species in mesomediterranean habitats, Muscina levida (Harris) (Diptera: Muscidae) the dominant species in supramediterranean habitats, and Prochyliza nigrimana (Meigen) (Diptera: Piophilidae) the dominant species in oromediterranean habitats. Differences in assemblage composition were also found among seasons. Thermophobic species such as Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) and some species of Heleomyzidae were well represented during autumn, winter and spring in the three bioclimatic levels sampled. By contrast, thermophilic species such as Ch. albiceps and Lucilia sericata (Meigen) (Diptera: Calliphoridae) and most Muscidae and Sarcophagidae species were more abundant during summer and in mesomediterranean habitats located at lower elevations. Knowledge of the preferences of some species for certain habitats may be of ecological and forensic value and may establish a starting point for further research.
Keywords: Animals; Biota; climate; Diptera; Diptera: classification; Diptera: physiology; Ecosystem; Forensic entomology; habitat association; sarcosaprophagous Diptera; Seasons; Spain

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species

Assessing the effects of vegetation type on hoverfly (Diptera: Syrphidae) diversity in a Mediterranean landscape: implications for conservation - Ricarte, Antonio; Ángeles Marcos-García, M; Moreno, Claudia E (Journal of Insect Conservation, 2011)
Understanding the responses of insects to ecological variables provides information that is fundamental for their conservation. The present study took place in three different landscapes (three plots of 10 9 10 km each) in a typical Mediterranean ecosystem of a Spanish national park. Each landscape included three vegetation types, grasslands, scrublands, and woodlands, and was characterised by a dominant vegetation type. Our objectives were: (1) to assess how important the inﬂuence of the dominant vegetation type and the vegetation type of sites are on hoverﬂy (Diptera: Syrphidae) diversity at landscape scale; (2) to assess whether scrublands are contributing to the loss of hoverﬂy diversity in an ecosystem with a long history of human use. In order to achieve these goals, we compared hoverﬂy diversity among sampling sites by prospecting all three diversity levels, alpha, beta and gamma, at each landscape. We sampled adult hoverﬂies at 18 sites located in different vegetation types within the three landscapes. No evidence was found that demonstrated an effect of the dominant vegetation type on alpha or beta diversity of sites, but the vegetation type of sites did have an affect. The highest species richness was found in woodland sites, particularly in the grassland-dominated landscape. At each landscape, beta diversity among sampling sites contributed more to gamma diversity than alpha diversity did. Our results highlight the need to focus on the conservation of woodland remnants of grassland-dominated landscape and scrubland-dominated landscape in order to preserve a large proportion of the biodiversity of Caban˜eros hoverﬂies, as well as on the maintenance of the mosaic landscape, which is linked to high beta diversity, typical in many Mediterranean ecosystems. We emphasise the importance of open clearings in the vast mass of scrubland in the scrubland-dominated landscape in order to provide extra resources for the hoverﬂies.
Keywords: alpha beta and gamma diversity; grassland; national park; scrubland; Spain; woodland

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest

Opportunities and Constraints for Climate Adaptation in Regional Water and Land Use Planning - Werners, S E; West, J; Leemans, R; Tabara, J D; Dai, X; Flachner, Z; Neufeldt, H; McEvoy, D; Cots, F; Trombi, G (The Economic, Social and Political Elements of Climate Change, 2011)
Whereas the literature on adaptation is rich in detail on the impacts of, vulnerability to, and constraints of climate adaptation, less is known about the conditions that facilitate adaptation in practice. We examined the constraints and opportunities for adaptation in water and land use planning in three regions: the Guadiana River Basin in Spain and Portugal, the Tisza River Basin in Hungary and western Inner Mongolia in China. We analysed the conditions that either facilitate or constrain adaptation in relation to (1) adaptation actors, (2) adaptation strategies, and (3) adaptation objectives. Many adaptation assessments concentrate on climate impacts and the potential of adaptation strategies. The conditions that enable people to act on adaptation are less studied. Yet these have been identified as particularly important for successfully implementing adaptation. We find that adaptation is enhanced by pilot projects that test and debate new ideas through collaboration between recognized actors from civil society, policy, and science. Promising for adaptation is the integration of (traditional) agro-environmental land use systems that regulate regional climate impacts with new technologies, organizational responsibilities and financial instruments. A key challenge is to create flexible and equitable financial instruments that facilitate benefit and burden sharing, social learning, and that support a diverse set of potentially better adapted new activities rather than compensate for climate impacts on existing activities
Keywords: Adaptation assessment; China; Climate adaptation; EUROPE; Hungary; Land use management; Portugal; Regional water and land use planning; Spain; Water management

Rapid characterization of dry cured ham produced following different PDOs by proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). - Del Pulgar, José Sánchez; Soukoulis, Christos; Biasioli, Franco; Cappellin, Luca; García, Carmen; Gasperi, Flavia; Granitto, Pablo; Märk, Tilmann D.; Piasentier, Edi; Schuhfried, Erna (Talanta, 2011)
In the present study, the recently developed proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS) technique was used for the rapid characterization of dry cured hams produced according to 4 of the most important Protected Designations of Origin (PDOs): an Iberian one (Dehesa de Extremadura) and three Italian ones (Prosciutto di San Daniele, Prosciutto di Parma and Prosciutto Toscano). In total, the headspace composition and respective concentration for nine Spanish and 37 Italian dry cured ham samples were analyzed by direct injection without any pre-treatment or pre-concentration. Firstly, we show that the rapid PTR-ToF-MS fingerprinting in conjunction with chemometrics (Principal Components Analysis) indicates a good separation of the dry cured ham samples according to their production process and that it is possible to set up, using data mining methods, classification models with a high success rate in cross validation. Secondly, we exploited the higher mass resolution of the new PTR-ToF-MS, as compared with standard quadrupole based versions, for the identification of the exact sum formula of the mass spectrometric peaks providing analytical information on the observed differences. The work indicates that PTR-ToF-MS can be used as a rapid method for the identification of differences among dry cured hams produced following the indications of different PDOs and that it provides information on some of the major volatile compounds and their link with the implemented manufacturing practices such as rearing system, salting and curing process, manufacturing practices that seem to strongly affect the final volatile organic profile and thus the perceived quality of dry cured ham.
The following values have no corresponding Zotero field: accession-num: 21645714
Keywords: Animals; Data Mining; Dry cured ham; Flavour compounds; Food Handling; Food Handling: methods; Italy; Mass spectrometry; Mass Spectrometry: methods; Meat Products; Meat Products: analysis; PDO; PTR-MS; PTR-ToF-MS; Spain; Swine; volatile compounds; Volatile Organic Compounds

The use of forest resources in central Iberia during the Late Iron Age. Insights from the wood charcoal analysis of Pintia, a Vaccaean oppidum - Rubiales, Juan M; Hernández, Laura; Romero, Fernando; Sanz, Carlos (Journal of Archaeological Science, 2011)
Charred woods may be used to effectively reconstruct past wood acquisition strategies. We used anthracological data from the pre-Roman settlement of Pintia (Padilla de Duero, Valladolid) to examine the use of forest resources at the local scale. Palaeoecological data revealed heterogeneous landscapes in the inland northern meseta with environments that offered diverse sources of wood for the inhabitants of Pintia, one of the ﬁrst cities of inland Iberia. Pines (Pinus pinea/pinaster and Pinus sylvestris/nigra) and both evergreen and deciduous Quercus L. and Juniperus L. were the main taxa identiﬁed as both fuelwood and construction elements, but the assemblages and frequencies of these taxa differed depending on their use. We also examined the potential of models from human ecology by considering the frequency, handling time and the relative technological value of each taxon to model how people gathered wood resources. The results suggest that although local availability affected the forest resources that were used by the Vaccaei people, speciﬁc taxa were positively selected for speciﬁc uses
Keywords: Anthracology; Holocene; Human behavioral ecology; Northern meseta; Palaeoethnobotany; Spain; Wood use

Effects of forest management on epiphytic lichen diversity in Mediterranean forests - Aragón, Gregorio; Martinez, I.; Izquierdo, P.; Belinchon, R.; Escudero, A. (APPLIED VEGETATION SCIENCE, 2010)
Question What are the responses of epiphytic lichens to the intensity of management along a large environmental gradient in Mediterranean Quercus forests? Location Central Spain. Methods This study was carried out on 4590 trees located in 306 forest stands dominated by Quercus faginea or Quercus ilex ssp. ballota. The effect of forest management and other predictor variables on several species diversity indicators were studied. Variables modelled were total species richness, cyanolichen richness and community composition. A large number of predictor variables were included: forest fragmentation (patch size, stand variability), climate and topographic (altitude, slope, sun radiation, annual rainfall and mean annual temperature) and intensity of management. General linear models and constrained ordination techniques were used to model community traits and species composition, respectively. Results Total richness and especially cyanolichens richness were significantly and negatively affected by the intensity of management. Lichen composition was influenced by management intensity, climatic and topographic variables and stand variability. Conclusions In Mediterranean forests, human activities related to forestry, agricultural and livestock use cause impoverishment of lichen communities, including the local disappearance of the most demanding species. The conservation of unmanaged forests with a dense canopy is crucial for lichen diversity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Community traits; Cyanolichens; Drivers of composition; fragmentation; land use; oak forests; Spain; Variation partitioning

The historical origins of aridity and vegetation degradation in southeastern Spain - Carrión, J. S. S.; Fernández, S.; Jiménez-Moreno, G.; Fauquette, S.; Gil-Romera, G.; González-Sampériz, P.; Finlayson, C. (Journal of Arid Environments, 2010)
The complex relationships within modern landscapes cannot be understood without the beneﬁt of retrospective studies. We review palaeoenvironmental data for southeastern Spain, a landscape vulnerable to desertiﬁcation and with antiquity of human pressure on the landscape. A xerophytic component is discernible in the pollen diagrams of the southeastern peninsula ever since the Middle Miocene. During glacial stages of the Pleistocene, mountain grasslands and lowland steppes expanded, but tree vegetation, although episodically contracted, was ever present across the region, explaining part of the modern plant-species diversity. The magnitude of human impacts on vegetation during the Holocene has been highly variable, starting earlier (e.g. after c. 5000 cal years BP) in low-elevation areas and river basins. Forest degradation of the mountains started rather late during the Argaric period, and reached its maximum during the Roman occupation. Over the last millennia, natural and/or human-set ﬁres, combined with overgrazing, probably have pushed forests over a threshold leading to the spread of grassland, thorny scrub, junipers, and nitrophilous communities. The high degree of xerophytization observed today in southeastern Spain results from the long-term determinism of the Mid to Late Holocene climate aridiﬁcation, and the contingency of historical factors like ﬁre events and changes in prehistoric local economies involving resource exhaustion.
Keywords: historical biogeography; Holocene; palaeoecology; quaternary; Spain; Tertiary

Past tree range dynamics in the Iberian Peninsula inferred through phylogeography and palaeodistribution modelling: A review - Rodríguez-Sánchez, Francisco; Hampe, Arndt; Jordano, Pedro; Arroyo, Juan (Review of Palaeobotany and Palynology, 2010)
The forests in the Iberian Peninsula have been strongly inﬂuenced by past climatic changes, but reconstructing their historical distributions and dynamics is very difﬁcult due to the complex climatic characteristics and relief of the region. Research disciplines such as phylogeography and species distribution modelling can describe the past range dynamics of individual tree species in relatively great detail and help elucidate how these species have reacted to climatic changes. Here we review phylogeographical and modelling studies from species representative of the major Iberian forest types and attempt to extract general trends from the diversity of individual species histories in the Peninsula. To date most studies focus on geographical range dynamics during the Pleistocene, but an increasing body of evidence shows that some species have also retained the genetic imprints of much more ancient processes. Many widespread Iberian species show a deep and often remarkably clear-cut divide between populations from the Mediterranean and from the Atlantic regions of the Iberian Peninsula, suggesting that both areas have independently sustained viable populations over extended periods. In fact, phylogeographical studies commonly ﬁnd that species had several glacial refugia across the Iberian Peninsula. On the other hand, distribution models help identifying further suitable areas that could have sustained so far undetected refugia. Such studies are of interest for species conservation, because refugium populations are high-priority targets due to their longterm persistence and unique evolutionary trajectory. Overall, we conclude that palaeoecology, phylogeography and species distribution modelling have a great potential to inform each other because of their complementary perspectives and results. A true integration of these approaches is therefore fundamental for further progress in our understanding of past Iberian environments and the organisms they harboured.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: genetic diversity; glacial refugia; hindcasting; palaeobiogeography; Spain; species distribution modelling

Pharmaceutical ethnobotany in the western part of Granada province (southern Spain): ethnopharmacological synthesis. - Benítez, G.; González-Tejero, M. R.; Molero-Mesa, J. (Journal of ethnopharmacology, 2010)
The aim of this work is to catalogue, document, and make known the uses of plants for folk medicine in the western part of the province of Granada (southern Spain). An analysis was made of the species used, parts of the plant employed, preparation methods, administration means, and the ailments treated in relation to pathological groups. Materials and methods: The work was performed in 16 municipalities within the study zone. The partici- pants were located mainly by questionnaires distributed in public and private centres. The information, gathered through semi-structured open interviews of a total of 279 people, was included in a database for subsequent analysis.Afloristic catalogue of the territorywascompiled, enabling analyses of the relevance of certain botanical families in popular medicine. Results and conclusions: Great diversity was established among medicinal species in the region. A total of 229 species of plants were catalogued for use in human medicine to prevent or treat 100 different health problems covering 14 different pathological groups. The number of references reached 1963. The popular pharmacopoeia of this area relies primarily on plants to treat digestive, respiratory, and circulatory problems, using mainly the soft parts of the plant (leavesandflowers)prepared in simpleways (decoction, infusion). An analysis of the medicinal ritual uses of 34 species and the different symptoms reflected a certain acculturation in relation to ethnobotanical knowledge in the last 20 years. Ethnopharmacological relevance: The traditional knowledge of plants was shown in relation to medicinal use, reflecting a striking diversity of species and uses, as well as their importance in popular plant therapy in the study zone. These traditions could pave the way for future phytochemical and pharmacological studies and thereby give rise to new medicinal resources.
The following values have no corresponding Zotero field: accession-num: 20226847
Keywords: Acculturation; Ethnopharmacology; Folk medicine; Granada; Medicinal plants; Spain

Quantitatively defining the conservation status of Natura 2000 forest habitats and improving management options for enhancing biodiversity - Hernando, Ana; Tejera, Rosario; Velazquez, Javier; Núñez, María Victoria (Biodiversity and Conservation, 2010)
The main goal of Natura 2000 network is to guarantee the favourable conservation status of habitats and species ensuring European biodiversity. As a result, certain forest areas have been included in this network listed as 9230-Quercus pyrenaica habitat and 9340-Quercus ilex subsp. rotundifolia forest habitat. These areas were previously used for ﬁrewood extraction or livestock grazing and browsing. Nowadays these habitats are coppice forests with asexual regeneration, which is far from the desired conservation status. Traditional timber harvesting plans do not take account of the new objectives required for these Natura sites, which attempt to ensure biodiversity and recreational uses instead of simply focusing on timber production. This paper proposes a ﬂexible methodology (applied to the study area ‘‘Dehesa Boyal’’ in A´ vila, Spain) for managing Natura 2000 forest sites by stands for sustainable forest management and the new requirements. The methodology has two phases. The ﬁrst, ‘‘Division of the forest area into stands’’, deﬁnes homogeneous patches of vegetation distinct in species composition, physiognomic structure and future management. The second, ‘‘Conservation status assessment of stands’’, quantiﬁes the conservation status of each previously classiﬁed stand considering a series of factors such as: functional health, restoration, ﬂoral richness and structure. A total value integrating the conservation status of stands is then calculated for the habitat. Both phases use Geographic Information System tools for managing information and visualizing results. The proposed methodology provides forest managers with a good knowledge of the territory and subsequently enables them to take appropriate conservation measures to maintain biodiversity.
Keywords: Adaptive management; Asexual regeneration; Cattle; Coppice forest; GIS; Mediterranean biogeographic region; oak; Quercus pyrenaica; Spain; Stand

RUNOFF PRODUCTION AND EROSION PROCESSES ON A DEHESA IN WESTERN SPAIN* - Ceballos, Antonio; Cerdà, A.; Schnabel, Susanne (Geographical Review, 2010)
Runoff generation and soil erosion were investigated at the Guadalperal6n ex- perimental watershed (western Spain), within the land-use system known as dehesa, or open, managed evergreen forests. Season and type of surface were found to control runoff and soil- loss rates. Five soil units were selected as representative of surface types found in the study area: hillslope grass, bottom grass, tree cover, sheep trails, and shrub cover. Measurements were made in various conditions with simulated rainfall to gain an idea of the annual varia- tion in runoff and soil loss. Important seasonal differences were noted due to surface cover and moisture content of soil, but erosion rates were determined primarily by runoff. Surfaces covered with grass and shrubs always showed less erosion; surfaces covered with holm oaks showed higher runoff rates, due to the hydrophobic character of the soils. Concentrations of runoff sediment during the siniulations confirmed that erosion rates at the study site de- pended directly on the sediment available on the soil surface
Keywords: Dehesa; erosion; land use; rainfall simulation; runoff; Spain

Seasonal trends and spatial relations between environmental/meteorological factors and leishmaniosis sand fly vector abundances in Central Spain - Galvez, R.; Descalzo, M. A.; Miro, G.; Jimenez, M. I.; Martin, O.; Dos Santos-Brandao, F.; Guerrero, I.; Cubero, E.; Molina, R. (ACTA TROPICA, 2010)
This paper reports on an entomological survey performed over the period 2006-2008 in Central Spain (mainly in the Madrid province) where canine leishmaniosis (CanL) is endemic. The study area was selected on the grounds of its wide altitude range, which determines both broad climate and vegetation ranges that could affect sand fly distributions. This area was surveyed from NE to SW across its mountain range (Sistema Central) and plateau area using sticky traps mainly on embankments. In 2006 and 2007, 123 sites were sampled (9557 sand flies captured) to establish possible relations between environmental or meteorological factors and vector densities (Phlebotomus perniciosus and Phlebotomus ariasi). The factors correlated with higher vector densities were: a sample site between villages or at the edge of a village, the lack of a paved road, a rural habitat, an east or south-facing wall or wall sheltered from the wind, the presence of livestock or birds, a holm-oak wood vegetation, a lower summer mean temperature and lower annual mean precipitation. This study was followed by a seasonal survey conducted at 16 selected sites (14,353 sand flies) sampled them monthly from May to November 2008. P. perniciosus showed a diphasic seasonal trend with two abundance peaks in July and September whereas P. ariasi showed a monophasic trend with one peak in August. Comparing with data from studies performed in 1991 in the same area, vector densities are significantly higher. A possible explanation for this is that the vectors (mainly P. ariasi) are moving towards higher altitudes perhaps because of global change. This increasing trend could have an impact on CanL and its geographical distribution. (C) 2010 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: Canine leishmaniosis; Environmental and meteorological factors; Phlebotomus ariasi; Phlebotomus perniciosus; Sand fly vector; Spain

Acorn crop size and pre-dispersal predation determine inter-specific differences in the recruitment of co-occurring oaks. - Espelta, Josep Maria; Cortes, P.; Molowny-Horas, R.; Retana, J. (Oecologia, 2009)
The contribution of pre-dispersal seed predation to inter-specific differences in recruitment remains elusive. In species with no resistance mechanisms, differences in pre-dispersal predation may arise from differences in seed abundance (plant satiation) or in the ability of seeds to survive insect infestation (seed satiation). This study aimed to analyse the impact of pre-dispersal acorn predation by weevils in two co-occurring Mediterranean oaks (Quercus ilex and Quercus humilis) and to compare its relevance with other processes involved in recruitment. We monitored the patterns of acorn production and acorn infestation by weevils and we conducted experimental tests of acorn germination after weevil infestation, post-dispersal predation and seedling establishment in mixed forests. Monitoring and experimental data were integrated in a simulation model to test for the effects of pre-dispersal predation in recruitment. In both oaks pre-dispersal acorn infestation decreased with increasing acorn crop size (plant satiation). This benefited Q. ilex which exhibited stronger masting behaviour than Q. humilis, with almost a single and outstanding reproductive event in 6 years. Acorn infestation was more than twice as high in Q. humilis (47.0%) as in Q. ilex (20.0%) irrespective of the number of seeds produced by each species. Although germination of infested acorns (seed satiation) was higher in Q. humilis (60%) than in Q. ilex (21%), this could barely mitigate the higher infestation rate in the former species, to reduce seed loss. Conversely to pre-dispersal predation, no inter-specific differences were observed either in post-dispersal predation or seedling establishment. Our results indicate that pre-dispersal predation may contribute to differences in seed supply, and ultimately in recruitment, between co-existing oaks. Moreover, they suggest that seed satiation can barely offset differences in seed infestation rates. This serves as a warning against overemphasising seed satiation as a mechanism to overcome seed predation by insects.
The following values have no corresponding Zotero field: accession-num: 19544074
Keywords: Animals; Feeding Behavior; Feeding Behavior: physiology; germination; Germination: physiology; Models, Biological; Quercus; Quercus: physiology; Seeds; Seeds: growth & development; Spain; Species Specificity; weevils; Weevils: physiology

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Effectiveness of rodents as local seed dispersers of Holm oaks. - Gómez, José M; Puerta-Piñero, Carolina; Schupp, Eugene W (Oecologia, 2008)
In this study we assessed the effectiveness of rodents as dispersers of Quercus ilex in a patchy landscape in southeastern Spain. We experimentally followed the fates of 3,200 marked and weighed acorns from dispersal through the time of seedling emergence over three years. Rodents handled about 99% of acorns, and dispersed 67% and cached 7.4% of the dispersed acorns. Most caches were recovered and consumed, and only 1.3% of the original experimental acorns were found alive in caches the following spring. Dispersal distances were short (mean = 356.2 cm, median = 157 cm) and strongly right-skewed. Heavier acorns were dispersed further and were more likely to be cached and survive than lighter acorns. All caches were in litter or soil, and each contained a single acorn. Rodents moved acorns nonrandomly, mostly to oaks and pines. Most surviving acorns were either in oaks, a poor microhabitat for oak recruitment, or shrubs, a suitable microhabitat for oak recruitment. Our results suggest that rodents, by burying a relatively high proportion of acorns singly in shrubs and pines, act as moderately effective dispersers of Q. ilex. Nonetheless, this dispersal comes at a very heavy cost.
Keywords: Animals; Ecosystem; Feeding Behavior; germination; Germination: physiology; Quercus; Quercus: physiology; Rodentia; Rodentia: psychology; Seeds; Seeds: physiology; Soil; Spain

Silviculture and Carbon Sequestration in Mediterranean Oak Forests - Cañellas, I.; Sánchez-González, M.; Bogino, S. M.; Adame, P.; Herrero, C.; ROIG, S.; Paulo, J. A.; Bravo, F. (Managing Forest Ecosystems: The Challenge of Climate Change, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.
The following values have no corresponding Zotero field: periodical: Managing Forest Ecosystems: The Challenge of Climate Change, electronic-resource-num: 10.1007/978-1-4020-8343-3
Keywords: biomass; carbon stock; Kyoto protocol; Portugal; Spain

Silviculture and Carbon Sequestration in Mediterranean Oak Forests - Cañellas, I; Sanchez-Gonzalez, M; Bogino, S M; Adame, P; Herrero, C; Roig, S; Paulo, J A; Bravo, F (Managing Forest Ecosystems: The Challenge of Climate Change, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.
Keywords: biomass; carbon stock; Kyoto protocol; Portugal; Spain

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a. (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

A new endophytic species of Preussia (Sporormiaceae) inferred from morphological observations and molecular phylogenetic analysis - Arenal, Francisco; Platas, Gonzalo; Pelaez, Fernando (FUNGAL DIVERSITY, 2007)
A new species of Preussia as an endophyte of different typical Mediterranean plant species is newly described and illustrated based on molecular and morphological features. Preussia mediterranea resembles P. australis, P. africana and P. similis from a morphological point of view, but appeared closer to P. minima and P. isabellae by molecular analysis. Phylogenetic analysis of the entire ITS region combined with the D1-D2 domains of the 28S rRNA gene, and a fragment of the elongation factor EF-1 alpha gene, using Maximum Likelihood and a Bayesian Markov Chain Monte Carlo approach, generally resulted in statistically well-supported clades for all the species studied. Morphological data and molecular phylogenetic analysis supported the recognition of the new taxon.
The following values have no corresponding Zotero field: pub-location: NORTHEAST FORESTRY UNIV, HARBIN, 00000, PEOPLES R CHINA publisher: FUNGAL DIVERSITY PRESS
Keywords: Ascomycota; Bayesian analysis; elongation factor; ITS; LSU; maximum likelihood; phylogeny; rDNA; Spain; Sporormiaceae; taxonomy

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
The following values have no corresponding Zotero field: accession-num: 16648953
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Series de deflactores corcheros desde 1900 - Blanco, S. Zapata (2006)
The aim of this work is to elaborate series of deflators, for whole twentieth century, of three representative products in the cork business: raw cork, corkwood in planks and stoppers of natural cork. Given that prices of these products are not available, the data bases for reconstruction are, on one hand, unitary values of production and exports from Portugal and Spain and, on the other hand, unitary ones of United Kingdom’s imports. By using these values, selected after different tests of coherence and credibility, Laspeyres, Paasche and Fisher’s indexes and a “synthetic cork deflator” are calculated. Then, a preliminary analysis about the unitary values as a proxy to the prices during the second half of twentieth century is realized. At last, the main figures which have been employed to the building of the deflators are shown in a statistical appendix.
The following values have no corresponding Zotero field: secondary-title: Asociación Española de Historia Económica periodical: Asociación Española de Historia Económica
Keywords: Cork; Deflators; Portugal; Spain; Twentieth century

Series de deflactores corcheros desde 1900 - Blanco, S Zapata (Asociación Española de Historia Económica, 2006)
The aim of this work is to elaborate series of deflators, for whole twentieth century, of three representative products in the cork business: raw cork, corkwood in planks and stoppers of natural cork. Given that prices of these products are not available, the data bases for reconstruction are, on one hand, unitary values of production and exports from Portugal and Spain and, on the other hand, unitary ones of United Kingdom’s imports. By using these values, selected after different tests of coherence and credibility, Laspeyres, Paasche and Fisher’s indexes and a “synthetic cork deflator” are calculated. Then, a preliminary analysis about the unitary values as a proxy to the prices during the second half of twentieth century is realized. At last, the main figures which have been employed to the building of the deflators are shown in a statistical appendix.
Keywords: Cork; Deflators; Portugal; Spain; Twentieth century

Application of central-place foraging theory shows the importance of Mediterranean dehesas for the conservation of the cinereous vulture, - Carrete, M.; Donazar, J. (Biological Conservation, 2005)
The dehesa (oak woodland) is an extensive agro-pastoral ecosystem characteristic of the Western Mediterranean countries which is suVering a great transformation process since 1950. Although its distribution largely overlaps with several endangered species, there is scarce information on how they use this human-transformed habitat. We studied the foraging habitat selection of one of them, the cinereous vulture Aegypius monachus. We radio-tracked 14 cinereous vultures in one of the largest European colonies from 1998 to 2000. Used and available habitats were compared at two scales using compositional analysis. Moreover, we developed a distance-based GLMM for assessing habitat selection in this central-place forager species, by taking into account the spatial distribution of habitat patches in relation to the location of the colony. Home ranges overlapped over a total surface of 592,527 ha around the colony, and both individual home ranges and travel foraging distances (mean 27.86 km, maximum 86 km) were larger during the breeding season. All cinereous vultures avoided agricultural lands within their home ranges throughout the year. Habitat use in relation to the distance to the colony pointed out that dehesas were positively selected in spite of being on average far away from the colony than other habitats, a result that was consistent among individuals and seasons. The cinereous vulture thus depends for its conservation not only on the protection of breeding areas, as has been so far considered, but also on the maintenance of well-conserved dehesas close to the colonies. Preserving the cinereous vultures could contribute to the economic sustainability of dehesas by attracting PAC funds for their traditional low-intensity exploitation. Although other species may also beneWt from this study since cinereous vulture could be a “Xagship” for the large-scale conservation of Mediterranean oak woodlands and associated biodiversity, more Wne local management guidelines should be performed on the basis of studies on more sensitive species.
Keywords: central-place forager; cinereous vulture; european common agricultural policy; large-scale conservation; Spain

Application of central-place foraging theory shows the importance of Mediterranean dehesas for the conservation of the cinereous vulture, - Carrete, M; Donazar, J (Biological Conservation, 2005)
The dehesa (oak woodland) is an extensive agro-pastoral ecosystem characteristic of the Western Mediterranean countries which is suVering a great transformation process since 1950. Although its distribution largely overlaps with several endangered species, there is scarce information on how they use this human-transformed habitat. We studied the foraging habitat selection of one of them, the cinereous vulture Aegypius monachus. We radio-tracked 14 cinereous vultures in one of the largest European colonies from 1998 to 2000. Used and available habitats were compared at two scales using compositional analysis. Moreover, we developed a distance-based GLMM for assessing habitat selection in this central-place forager species, by taking into account the spatial distribution of habitat patches in relation to the location of the colony. Home ranges overlapped over a total surface of 592,527 ha around the colony, and both individual home ranges and travel foraging distances (mean 27.86 km, maximum 86 km) were larger during the breeding season. All cinereous vultures avoided agricultural lands within their home ranges throughout the year. Habitat use in relation to the distance to the colony pointed out that dehesas were positively selected in spite of being on average far away from the colony than other habitats, a result that was consistent among individuals and seasons. The cinereous vulture thus depends for its conservation not only on the protection of breeding areas, as has been so far considered, but also on the maintenance of well-conserved dehesas close to the colonies. Preserving the cinereous vultures could contribute to the economic sustainability of dehesas by attracting PAC funds for their traditional low-intensity exploitation. Although other species may also beneWt from this study since cinereous vulture could be a “Xagship” for the large-scale conservation of Mediterranean oak woodlands and associated biodiversity, more Wne local management guidelines should be performed on the basis of studies on more sensitive species.
Keywords: central-place forager; cinereous vulture; european common agricultural policy; large-scale conservation; Spain

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G. (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
The following values have no corresponding Zotero field: accession-num: 15997399
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernandez-Llario, P.; Mateos-Quesada, P.; Silvério, A.; Santos, P. (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernández-Llario, P; Mateos-Quesada, P; Silvério, A; Santos, P (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M Blanca Ruiz; Jos, M; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M. Blanca Ruiz; Jos, M.; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - Espelta, J. M.; Rodrigo, A.; Habrouk, A.; Meghelli, N.; Ordonez, J. L.; Retana, J. (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
The following values have no corresponding Zotero field: periodical: FIRE AND BIOLOGICAL PROCESSES pub-location: PO BOX 321, 2300 AH LEIDEN, NETHERLANDS
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - ESPELTA, J M; Rodrigo, a; Habrouk, A; Meghelli, N; Ordonez, J L; RETANA, J (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

The origin of the Sierra de Aracena Hollows in the Sierra Morena, Huelva, Andalucia, Spain - Espejo, J M Recio; Faust, D; Granados, M A Nuñez (Geomorphology, 2002)
Hollows in the Sierra de Aracena, part of western sector of Sierra Morena region (Huelva, Spain), are geoecologically unusual macroforms. They are underlain by deeply weathered bedrock but have eutrophic soils with distinctive vegetation. Paleosols with very dark colours, a predominance of smectites and large amounts of total and free iron occur on the floors on the hollows. An evolutionary model is proposed for the hollows, involving differential weathering during the Mesozoic on plutonic and amphibolitic rocks, alpine tectonic activity followed by Quaternary erosion and exhumation leading to formation of erosional terraces
Keywords: deep weathering; hercynian massif; hollows macroforms; sierra morena; Spain

The aero-aquatic Helicodendron microsporum n. sp from Mallorca, Spain - Abdullah, S. K.; Cano, J.; Descals, E.; Guarro, J. (MYCOLOGICAL RESEARCH, 2000)
A new aero-aquatic helicosporous hyphomycete, Helicodendron microsporum, is described and illustrated from decaying leaves submerged in a small artificial pond surrounded by Quercus ilex and Pinus halepensis in Mallorca, Spain. It is characterized by branched conidiophores with chains of hyaline conidia eventually forming white clusters which do not break up even at maturity. It also has small conidia (8-10 mu m diam.) consisting of a 2-2.5 mu m thick filament which coils 1.5-2 times counter-clockwise. The main characters of the species are compared with 14 similar hyalosporous Helicodendron species.
APSAPSThe following values have no corresponding Zotero field: pub-location: 40 WEST 20TH STREET, NEW YORK, NY 10011-4211 USA publisher: CAMBRIDGE UNIV PRESS
Keywords: deaying leaves; hyphomycete; Pinus halepensis; Quercus ilex; Spain

The aero-aquatic Helicodendron microsporum n. sp from Mallorca, Spain - Abdullah, S K; Cano, J; Descals, E; Guarro, J (MYCOLOGICAL RESEARCH, 2000)
A new aero-aquatic helicosporous hyphomycete, Helicodendron microsporum, is described and illustrated from decaying leaves submerged in a small artificial pond surrounded by Quercus ilex and Pinus halepensis in Mallorca, Spain. It is characterized by branched conidiophores with chains of hyaline conidia eventually forming white clusters which do not break up even at maturity. It also has small conidia (8-10 mu m diam.) consisting of a 2-2.5 mu m thick filament which coils 1.5-2 times counter-clockwise. The main characters of the species are compared with 14 similar hyalosporous Helicodendron species.
APS
Keywords: deaying leaves; hyphomycete; Pinus halepensis; Quercus ilex; Spain

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J. S.; Geel, B. Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J S; Geel, B Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

Geographical and seasonal influences on the distribution of fungal endophytes in Quercus ilex - Collado, J; Platas, G; GONZÁLEZ, I; Pelaez, F (New Phytologist, 1999)
A systematic survey of the endophytic assemblages of Quercus ilex in central Spain has been performed, with the goal of evaluating the importance of geographical and seasonal factors on these fungal communities. Four sampling sites were selected; one of them was sampled twice, in the spring and the autumn. The collected plant material consisted of bark, twigs and leaves from eight trees per site. Fungal strains were isolated with the use of a surface-sterilization method with sodium hypochlorite. A total of 2921 fungal strains grouped into 149 ‘species’ or morphological types were recovered. The 10 dominant species, with isolation frequencies >1.5%, were Pyrenochaeta sp., Periconiella anamorph of Biscogniauxia mediterranea (De Not.) Kuntze, Pseudonectria sp., Cryptosporiopsis quercina Petrak, Alternaria alternata (Fr:) Keissl., two undetermined coelomycetes, Penicillium funiculosum Thom, Diplodia mutila Fr. apud Mont. and Ascochyta sp. Medians of fungal species per tree were significantly different among the sampled sites. The isolation frequencies of the dominant species, as well as other less frequent species, were significantly dependent on the sampling site. The degree of endophytic infection and the diversity of fungal species were significantly higher in the spring. The frequencies of all dominant species at one of the sites depended significantly on the season, except for C. quercina, Acremonium sclerotigenum (F & V Moreau ex Valenta) Gams. and D. mutila. Cluster analysis of the whole endophytic mycoflora of the sampled trees suggested that the geographical factor affects the endophytic distribution patterns more significantly than the seasonal factor.
Keywords: fungal endophytes; geographical distribution; Quercus ilex; seasonal distribution; Spain

Geographical and seasonal influences on the distribution of fungal endophytes in Quercus ilex - Collado, J.; Platas, G.; GONZÁLEZ, I.; Pelaez, F. (New Phytologist, 1999)
A systematic survey of the endophytic assemblages of Quercus ilex in central Spain has been performed, with the goal of evaluating the importance of geographical and seasonal factors on these fungal communities. Four sampling sites were selected; one of them was sampled twice, in the spring and the autumn. The collected plant material consisted of bark, twigs and leaves from eight trees per site. Fungal strains were isolated with the use of a surface-sterilization method with sodium hypochlorite. A total of 2921 fungal strains grouped into 149 ‘species’ or morphological types were recovered. The 10 dominant species, with isolation frequencies >1.5%, were Pyrenochaeta sp., Periconiella anamorph of Biscogniauxia mediterranea (De Not.) Kuntze, Pseudonectria sp., Cryptosporiopsis quercina Petrak, Alternaria alternata (Fr:) Keissl., two undetermined coelomycetes, Penicillium funiculosum Thom, Diplodia mutila Fr. apud Mont. and Ascochyta sp. Medians of fungal species per tree were significantly different among the sampled sites. The isolation frequencies of the dominant species, as well as other less frequent species, were significantly dependent on the sampling site. The degree of endophytic infection and the diversity of fungal species were significantly higher in the spring. The frequencies of all dominant species at one of the sites depended significantly on the season, except for C. quercina, Acremonium sclerotigenum (F & V Moreau ex Valenta) Gams. and D. mutila. Cluster analysis of the whole endophytic mycoflora of the sampled trees suggested that the geographical factor affects the endophytic distribution patterns more significantly than the seasonal factor.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: fungal endophytes; geographical distribution; Quercus ilex; seasonal distribution; Spain

Habitat correlates of European rabbit (Oryctolagus cuniculus) distribution after the spread of RVHD in Cadiz Province, Spain - Fa, John E; Sharples, Colin M; Bell, Diana J (Journal of Zoology, 1999)
European rabbit Oryctolagus cuniculus abundance was evaluated relative to habitat variables within two zones in Cadiz Province (south-east Spain), 2 years after the spread of rabbit viral haemorrhagic disease (RVHD). The study areas were low-lying regions of mixed pasture/agriculture, Mediterranean forest and matorral, west (Zone A) and east (Zone B) of the Sierra de Cadiz mountain chain. A total of 111 sites was selected to sample all existing habitat types. Relative rabbit density in each site was estimated using a pellet count method in one 5062 m transect. Mean pellet densities were 21.05 pellet m -2 in Zone B and signi®cantly lower, 5.85 pellets m -2 in Zone A. Physical variables, such as vegetation characteristics (density, height and patchiness of cover-layer vegetation, etc.), topographical characteristics and human in¯uences, cover-layer vegetation species (woody stemmed shrub species or trees forming dense stands), and ground-layer vegetation species (herbaceous species forming a low-lying layer) were determined within transects. In addition to these variables, soil types, rock type and land form, as well as the presence of aquifers, irrigation, and the proximity of rivers, were determined for each site. Signi®cantly higher pellet densities were found in mixed grassland/matorral and cork oak/matorral than in all other habitats. Pellet density was negatively correlated with density of ground-layer vegetation, while high pellet densities were associated with medium-height ground-layer vegetation (50±100 cm). The presence of Entisols was negatively associated with pellet density. The cover-layer species Pistacia lentiscus, Quercus coccifera, Quercus suber, Opuntia ®cus-indica and the ground-layer grasses all showed positive associations with pellet density, while the ground-layer species Echium gaditana and Scorpiurus vermiculatus were negatively associated with pellet density. Multivariate analyses identi®ed the mixed grassland/matorral and cork oak forest/matorral habitats as explaining most of the variation in pellet density. The height of cover-layer vegetation was negatively associated, while Opuntia and table-and/calcareous sandstone were positively associated, with mixed grassland/matorral. Distance from habitation and human impact were negatively associated and Quercus suber was positively associated with cork oak forest/matorral. Com- parison with previous studies suggest that the low pellet counts in this study represent very low rabbit densities and the population as a whole appears depleted and fragmented
Keywords: habitat; oryctolagus cuniculus; rabbit viral haemorrhagic disease; Spain

Habitat correlates of European rabbit (Oryctolagus cuniculus) distribution after the spread of RVHD in Cadiz Province, Spain - Fa, John E.; Sharples, Colin M.; Bell, Diana J. (Journal of Zoology, 1999)
European rabbit Oryctolagus cuniculus abundance was evaluated relative to habitat variables within two zones in Cadiz Province (south-east Spain), 2 years after the spread of rabbit viral haemorrhagic disease (RVHD). The study areas were low-lying regions of mixed pasture/agriculture, Mediterranean forest and matorral, west (Zone A) and east (Zone B) of the Sierra de Cadiz mountain chain. A total of 111 sites was selected to sample all existing habitat types. Relative rabbit density in each site was estimated using a pellet count method in one 5062 m transect. Mean pellet densities were 21.05 pellet m -2 in Zone B and signi®cantly lower, 5.85 pellets m -2 in Zone A. Physical variables, such as vegetation characteristics (density, height and patchiness of cover-layer vegetation, etc.), topographical characteristics and human in¯uences, cover-layer vegetation species (woody stemmed shrub species or trees forming dense stands), and ground-layer vegetation species (herbaceous species forming a low-lying layer) were determined within transects. In addition to these variables, soil types, rock type and land form, as well as the presence of aquifers, irrigation, and the proximity of rivers, were determined for each site. Signi®cantly higher pellet densities were found in mixed grassland/matorral and cork oak/matorral than in all other habitats. Pellet density was negatively correlated with density of ground-layer vegetation, while high pellet densities were associated with medium-height ground-layer vegetation (50±100 cm). The presence of Entisols was negatively associated with pellet density. The cover-layer species Pistacia lentiscus, Quercus coccifera, Quercus suber, Opuntia ®cus-indica and the ground-layer grasses all showed positive associations with pellet density, while the ground-layer species Echium gaditana and Scorpiurus vermiculatus were negatively associated with pellet density. Multivariate analyses identi®ed the mixed grassland/matorral and cork oak forest/matorral habitats as explaining most of the variation in pellet density. The height of cover-layer vegetation was negatively associated, while Opuntia and table-and/calcareous sandstone were positively associated, with mixed grassland/matorral. Distance from habitation and human impact were negatively associated and Quercus suber was positively associated with cork oak forest/matorral. Com- parison with previous studies suggest that the low pellet counts in this study represent very low rabbit densities and the population as a whole appears depleted and fragmented
Keywords: habitat; oryctolagus cuniculus; rabbit viral haemorrhagic disease; Spain

Climatic classification and ordination of the Spanish Sistema Central: relationships with potential vegetation - Gavilán, R G; Fernández-González, F; Blasi, C (Plant Ecology, 1998)
Monthly precipitation and monthly mean temperature records from 255 meteorological stations in Central Spain (Spanish Sistema Central) were analyzed by cluster and principal component analyses. Classiﬁcation separated 14 groups according to altitude, geographical distribution, as well as the combination of rainfall and temperature. The ﬁrst cluster emerged as signiﬁcantly higher and colder than the second. Then, two ordinations were carried out: one for the 14 groups extracted from the classiﬁcation and a second for the total station pool. The second ordination was compared with potential natural vegetation data taken around each station. The ﬁrst ordination summarized the principal climatic characteristics of the Spanish Sistema Central: its behaviour is that of a typical Mediterranean mountainous territory combining summer aridity and variation of temperature with altitude and the inﬂuence of winter winds. The ordination of all stations reﬂected a thermal, rainfall and summer aridity gradient. Meteorological stations situated at the highest altitude or with highest precipitation records characterized by scrub communities or pine woods and Quercus pyrenaica forests, appeared well-separated along the ﬁrst two axes. Only the most thermophilous Q. rotundifolia associations could be clearly separated. The fourth axis was useful in clarifying some vegetation overlap of deciduous and sclerophyllous forests, along an east-west summer aridity gradient.
Keywords: climate; cluster analysis; potential vegetation; Precipitation; Principal component analysis; Spain; Temperature

Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions - Cagnin, M; Moreno, S; Aloise, G; Garofalo, G; Villafuerte, R; Gaona, P; Cristaldi, M (Journal of Biogeography, 1998)
A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Sélys-Longchamps, 1838), Apodemus sylvaticus (L., 1758), A. flavicollis (Melchior, 1834) and Mus musculus domesticus Schwarz & Schwarz, 1943. In Southern Spain 428 specimens belonging to five species were trapped: Suncus etruscus, Crocidura russula (Hermann, 1780), Microtus duodecimcostatus (de Sélys-Longchamps, 1839), Apodemus sylvaticus and Mus spretus Lataste, 1883. The relative density of small mammals occurring in the nine Spanish sampling stations was twice that recorded in the Italian stations; however the number of species recorded in the different biotopes show similar mean values, ranging from three to five in Andalusia and from three to six in Calabria. Apodemus sylvaticus was the dominant species in the Calabrian stations, whereas Crocidura russula prevailed in Andalusia. The biotic diversity values are very similar in the Calabrian and Andalusian biotopes. By contrast, the Insectivora/Rodentia ratio was always higher in Andalusia. The more xerophytic biotopes showed greater similarities between the communities in Southern Spain and Southern Italy, while the cooler biotopes differed between these two peninsulas.
Keywords: habitat type; Italy; peninsular effect; sclerophyll biome; Small mammal communities; Spain

Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions - Cagnin, M.; Moreno, S.; Aloise, G.; Garofalo, G.; Villafuerte, R.; Gaona, P.; Cristaldi, M. (Journal of Biogeography, 1998)
A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Sélys-Longchamps, 1838), Apodemus sylvaticus (L., 1758), A. flavicollis (Melchior, 1834) and Mus musculus domesticus Schwarz & Schwarz, 1943. In Southern Spain 428 specimens belonging to five species were trapped: Suncus etruscus, Crocidura russula (Hermann, 1780), Microtus duodecimcostatus (de Sélys-Longchamps, 1839), Apodemus sylvaticus and Mus spretus Lataste, 1883. The relative density of small mammals occurring in the nine Spanish sampling stations was twice that recorded in the Italian stations; however the number of species recorded in the different biotopes show similar mean values, ranging from three to five in Andalusia and from three to six in Calabria. Apodemus sylvaticus was the dominant species in the Calabrian stations, whereas Crocidura russula prevailed in Andalusia. The biotic diversity values are very similar in the Calabrian and Andalusian biotopes. By contrast, the Insectivora/Rodentia ratio was always higher in Andalusia. The more xerophytic biotopes showed greater similarities between the communities in Southern Spain and Southern Italy, while the cooler biotopes differed between these two peninsulas.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: habitat type; Italy; peninsular effect; sclerophyll biome; Small mammal communities; Spain

Datos sobre la flora y vegetación de la Serranía de Ronda (Málaga, España) - Pérez Latorre, A V; Navas, P; Navas, D; Gil, Yolanda; Cabezudo, Baltasar (Acta Botanica Malacitana, 1998)
New data on flora and vegetation in the Serranía de Ronda (Málaga, Andalusia, Spain). A floristic and phytosociologial study has been done in the Natural Park Sierra de las Nieves, placed in Málaga (Andalusia, Spain). A total of 1.400 taxa have been recorded, fom which we have pointed out and commented 36, due to their biological value as endemisms, rare, protected or endemic species or new records in the studied area. One new taxonomical combination is proposed: Ulex baeticus subsp. bourgaeanus. A total of 78 associations and communities have been recorded. New sintaxa are described: one alliance (Pino pinastri-Juniperion phoeniceae), 12 associations, 9 subassociations and one new combination. The 6 climactic series described with their main tree species, soil and bioclimatic range are the following: two series of Quercus suber (termo-mesomediterranean on schists), one of Quercus rotundifolia (mesomediterranean on limestones), one of Quercus pyrenaica (mcsomediterranean on schists), one of Quercus alpestris (supramediterranean on limestones) and one of Juniperus sabina (oromediterranean on limestones). The 5 edaphoxeric series described with their main tree species, soil and bioclimatic range are the following: two series of Abies pinsapo (meso-supramediterranean on perdotite rocks and dolomite), two series of Juniperus phoenicea (termo-meso-supramediterranean on marble, dolomite and limestones) and one of Pious pinaster (termo-mesomediterranean on peridotite rocks). The 5 riverine edaphoseries described with their main tree species, soil and water-level range are the following: one of Fraxinus angustifolia (summer-droughted rivers on limestones), two of Salix pedicellata (summer-droughted rivers on peridotite rocks, schists and limestones) and two of Nerium oleander (seasonal streams, on peridotite rocks, schists and limestones). Finally, the complete sintaxonomic scheme, with new sintaxa, combinations, hierarchycity and comments on the associations and communities is given
Keywords: Andalusia; Flora; Málaga; series; Serranía de Ronda; Spain; Vegetation

Pollen calendar of the city of Salamanca (Spain). Aeropalynological analysis for 1981-1982 and 1991-1992. - Hernández Prieto, M; Lorente Toledano, F; Romo Cortina, A; Dávila González, I; Laffond Yges, E; Calvo Bullón, A (Allergol Immunopathol (Madr), 1998)
We report a study on the contents of airborne pollen in the city of Salamanca (Spain) aimed at establishing a pollen calendar for the city for the yearly periods of maximum concentrations, relating these with quantifiable atmospheric variables over two two-year periods with an interval of 10 years between them: 1981-82 and 1991-92. The pollen was captured with Burkard spore-traps, based on Hirst's volumetric method. Determinations were made daily and were used to make preparations, previously stained with basic fuscin, for study under light microscopy at x 1,000 magnification. 946 preparations were analyzed, corresponding to the same number of days distributed over 150 weeks of the periods studied. The results afforded the identification of 48 different types of pollen grain: Grasses (Poaceae), Olea europea (olive), Quercus rotundifolia (Holm-oak), other Quercus spp. (Q. pyrenaica, Q. suber, Q. faginea, etc.), Cupressaceae (Cupressus sempervivens, C. arizonica, Juniperus communis etc.), Plantago (Plantago lanceolata, Plantago media, etc.), Pinaceae (Pinus communis, Abies alba, etc.), Rumex sp. (osier), Urtica dioica (nettle), Parietaria (Parietaria officinalis, P. judaica), Chenopodio-Amaranthaceae (Chenopodium sp., Amaranthus sp., Salsola kali, etc.), Artemisia vulgaris (Artemisia), other Compositae (Taraxacum officinalis, Hellianthus sp. etc.), Castanea sativa (Chestnut), Ligustrum sp. (privet), Betula sp. (birch), Alnus sp. (common alder), Fraxinus sp (ash), Populus sp. (poplar), Salix sp. (willow), Ulmus sp. (elm), Platanus sp. (plantain, plane), Carex sp. (sweet flag), Erica sp. (common heather), Leguminosae or Fabaceae:--Papillionaceae (Medicago sp.; Cercis sp., Robina sp.)--Cesalpinoideae Acacia sp. (Acacia),--Mimosoideae: Sophora japonica, Umbelliferae (Foeniculum sp., Cirsium sp., etc.), Centaurea sp., Cistus sp. (rock rose), Typha sp (bulrush), Mirtaceae (Myrtus communis), Juglans regia (Walnut), Galium verum, Filipendula sp. (spirea/drop wort), Rosaceae (Pyrus sp., Prunus sp., etc.), Tilia sp. (Linden), Morus sp. (mulberry), Taxus baccata (yew), Papaveraceae (Papaver rhoeas etc.), Labiata (Lavandula sp.), Cannabaceae (Humulus sp. etc.), Liliaceae (Lilium sp.), Echium sp. (viper's bugloss). The most abundant taxa, detected in the highest quantities (grains/m3 air), by order of counting were as follows: holm-oak, olive, grasses, Plantago and Parietaria. With the data obtained we have established a pollen calendar for Salamanca and report the period in which each type of pollen is found along the years and the periods with the highest airborne concentrations of such pollens. The diversity and the spectrum of the pollen in the city of Salamanca correspond to the typical plant communities found on the dehesas (large ranges of grasslands) of Castile, where Salamanca is located, although the wind directions and the peculiar climatic characteristics of the area govern the peaks of maximum presence of the different taxa. As examples, in the case of olive, which is cultivated at some distance from the city, its maximum presence coincides with south-westerly winds; in the case of grasses, the peaks of maximum counts coincide with a sharp rise in mean temperature, close to or higher than 20 degrees C and between five and six weeks after rainfall equal to or greater than 5 L/m2.
APS
Keywords: pollen concentrations; Spain

Cambios espaciales de las formaciones forestales mediterráneas ocurridos en los últimos cuarenta años - Regato, P; Castejon, M; TELLA, G; GIMÉNEZ, S; BARRERA, I; ROSSELLO, R ELENA- (II Congreso Forestal Español, 1997)
Partial results obtained fram a Spanish forest fonnation dynamics study are presented. Seven land squares located in different land classes, have been diacranically analyzed using aerial photointerpretation and spatial analysis with G.1.S. techniques. As an overall trend, polarization in forest pattem evolution has been detected: Fragmentation and diversification have occurred in coastal and/or periurban areas, and homogenization and extensification have occurred in inner and remote areas.
Keywords: forest dynamics; landscape ecology; Mediterranean; Spain

A landscape in transition: an historical perspective on a Spanish latifundist farm - Pérez, A S; Remmers, G G A (Agriculture, ecosystems & environment, 1997)
An agricultural landscape, as a social construction, is not static, but a reflection of the balance of social forces which influence the way in which the natural resources of the site are combined. To understand and evaluate the current configuration of a landscape, and to define and understand criteria according to which a future landscape may be designed, it is necessary to analyse its historical construction. In this paper we follow these steps, taking as a point of reference a farm in one of the most important agricultural regions of Spain, the Guadalquivir river valley in Andalucla. This region stands out for its high production potential, social inequity and environmental degradation. The paper describes global changes in the use of the land in this river valley over the past 3 centuries, and uses aerial photographs from 1956 and 1990 to outline changes on the 1150-ha Los Humosos farm, recently granted to a co-operative of land labourers after years of struggle for land. Through this change in tenure the criteria 'control' and 'distribution of benefits' are achieved. Nine other criteria derived from the historical analysis were used to compare four different farm design scenarios through multi-criteria programming, which was preceded by an assessment of the biogeophysical characteristics of the land. However, this appeared to be insufficient to cope with essential criteria such as landscape architecture and biodiversity, because minor landscape elements were neglected which are important starters for the design of an ecological infrastructure. Water, a problematic resource in Mediterranean agriculture, paradoxically turned out to be an important characteristic of these landscape elements. From historical, ecological and social perspectives, new proposals for farm landscape design must necessarily and radically break with the recent past. It appears, however, that to produce agricultural landscapes of quality in the Guadalquivir river valley would involve tough social struggle, that nonetheless is found to use the margins left over by the dominant socio-economic, cultural and political structures. Finally, an agro-ecological option is proposed as a transitional design
Keywords: ecological agriculture; History; land labourers; landscape; Mediterranean; Spain; water

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F. M.; Suarez, M. a; Pérez, A. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)The following values have no corresponding Zotero field: accession-num: 9032619
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suárez, M A; Pérez, A (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Pre-climax epiphyte communities of bryophytes and lichens in Mediterranean forests from the Central Plateau (Spain) - Fuertes, E; Burgaz, A R; Escudero, a (Plant Ecology, 1996)
The pre-climax epiphytic communities of forests from the Spanish Mediterranean region (Central Plateau) were studied by numerical and traditional floristic methods. One hundred phytosociological relev6s were analyzed through a classical numerical approach based on hard partitions improved by PCoA - Principal Coordinates Analysis - ordinations. Two groups easily related to two different suballiances included in Frullanion dilatatae Lecointe 1975, Ulotenion crispae (Barkman 1958)Lecointe 1975 and Fabronienionpusillae Barkman 1958 were detected. Two new syntaxa within the ass. Ortotrichetum lyeUii (Allorge 1922) Lecointe 1975 are proposed. Phytogeography, syntaxonomy and ecology of these communities are discussed.
Keywords: epiphyte communities; frullanion dilatatae; Mediterranean forests; numerical syntaxonomy; Spain

Effects of forest fragmentation on a guild of wintering passerines: the role of habitat selection - Tellería, J L; Santos, T (Biological conservation, 1995)
This study analyses the winter colonization of an archipelago of 31 forests (0.1-350 ha) in central Spain by the guild of pariforms (Parus, Aegithalos, Regulus, Sitta and Certhia). Two hypotheses are considered: (a) that birds with similar habitat preferences tend to disap- pear simultaneously with the reduction in forest size, leading to a ‘nested’ pattern of species distribution; or (6) that the species in the smallest forests are a random sample of those found in the larger ones. The results sup- port hypothesis (a). The species that depend on rela- tively scarce resources, such as tree trunks and junipers Juniperus thurifera (Sitta europaea, Certhia brachy- dactyla, Parus cristatus and P.ater) only occupied the largest forests. On the other hand, species that exploit abundant, ubiquitous resources, such as holm oak Quercus ilex foIiage (Regulus ignicapillus and Parus caeruleus), were distributed uniformly throughout all the fragments. These results emphasize the need for a better understand- ing of habitat selection by species when designing conser- vation strategies for fragmented populations.
Keywords: Forest fragmentation; habitat selection; Spain; wintering passerines

Primera cita ibérica de Brachypalpus valgus ( Panzer , 1798 ) y Chrysotoxum parmense Rondani , 1845 ( Diptera : Syrphidae ): caracterización polínica de su dieta * - Marcos-garcía, M A; Isidro, P M (Boln. Asoc. esp. Ent, 1995)
The first Iberian specimens of the genus Brachypalpus and species Chrysotoxum parmense ha ve been caught in the Font Roja Natural Park (Alicante, Spain). The presence of these two species and the Psilota anthracina, indícales the importance of this Mediterranean holm oak sheltering threatened species in nearby countries like France and Germany. The pollen Lypes found in the alimentary canal of syrphids, are indicated for the first time.
Keywords: Brachypalpus valgus; Chrysotoxum parmense; Font Roja Natural Park; pollen content; Spain; Syrphidae

Red deer (Cervus elaphus hispanicus) management in the dehesa system in central Extremadura, Spain - Vargas, J. D.; Calvo, J. C.; Aparicio, M. A. (Agroforestry systems, 1995)
In this paper we report the results of a study on the suitability of the dehesa (Mediterranean woodlands) as habitat of red deer (Cervus elaphus hispanicus) in a closed country estate of about 4300 ha total surface situated in the San Pedro Mountain, in Central Extremadura, Spain. We have described the d e e r management with respect to habitat, exploitation mode, deer feeding, population control and production of goods and services. It is concluded that the dehesa system is a rich natural resource that preserves and improves the degraded environment.
Keywords: antlers; Dehesa; red deer (Cervus elaphus); Spain; wildlife habitat

Red deer (Cervus elaphus hispanicus) management in the dehesa system in central Extremadura, Spain - Vargas, J D; Calvo, J C; Aparicio, M A (Agroforestry systems, 1995)
In this paper we report the results of a study on the suitability of the dehesa (Mediterranean woodlands) as habitat of red deer (Cervus elaphus hispanicus) in a closed country estate of about 4300 ha total surface situated in the San Pedro Mountain, in Central Extremadura, Spain. We have described the d e e r management with respect to habitat, exploitation mode, deer feeding, population control and production of goods and services. It is concluded that the dehesa system is a rich natural resource that preserves and improves the degraded environment.
Keywords: antlers; Dehesa; red deer (Cervus elaphus); Spain; wildlife habitat

Datos sobre la vegetación de andalucía. III. Series de vegetación caracterizadas por "Quercus suber" L. - Pérez Latorre, Andrés V.; Nieto, José M.; Cabezudo, Baltasar (Acta botánica malacitana, 1994)
Data about andalusian vegetation. III. Vegetation series with Quercus suber L. presence. Quercus suber woods are one of the natural forests with more diversity and more expanse in Andalusia (Spain). Quercus suber is a dominant or common species in eight vegetation series or subseries: Myrto communis-Querceto suberis S, Teucrio baetici-Querceto suberis S, Smilaci mauritanicae-Querceto rotundifoliae quercetoso suberis subsigmetum, Tamo communis-Oleeto sylvestris quercetoso suberis subsigmetum, San guisorbo hybridae-Querceto suberis S, Pyro bourgaeanae-Querceto rotundifoliae quercetoso suberis subsigmetum, Paeonio coriaceae-Querceto rotundifoliae quercetoso fagineae subsigmetum, var. of Quercus suber, Adenocarpo decorticantis-Querceto rotundifoliae quercetoso suberis subsigmetum. These vegetation series show peculiar sucesional dynamism of their communities depending on their traditional use, environmental factors and biogeographical location. Two new subasociations, Ulici eriocladi-Cistetum ladamferi cistetosum albidi and Phyllireo angustifoliae-Quercetum lusitanicae cytisetosurn tribracteojati, are described in this paper.
Keywords: Andalusia; Quercus suber woods; Spain; vegetation series

Datos sobre la vegetación de andalucía. III. Series de vegetación caracterizadas por "Quercus suber" L. - Pérez Latorre, Andrés V; Nieto, José M; Cabezudo, Baltasar (Acta botánica malacitana, 1994)
Data about andalusian vegetation. III. Vegetation series with Quercus suber L. presence. Quercus suber woods are one of the natural forests with more diversity and more expanse in Andalusia (Spain). Quercus suber is a dominant or common species in eight vegetation series or subseries: Myrto communis-Querceto suberis S, Teucrio baetici-Querceto suberis S, Smilaci mauritanicae-Querceto rotundifoliae quercetoso suberis subsigmetum, Tamo communis-Oleeto sylvestris quercetoso suberis subsigmetum, San guisorbo hybridae-Querceto suberis S, Pyro bourgaeanae-Querceto rotundifoliae quercetoso suberis subsigmetum, Paeonio coriaceae-Querceto rotundifoliae quercetoso fagineae subsigmetum, var. of Quercus suber, Adenocarpo decorticantis-Querceto rotundifoliae quercetoso suberis subsigmetum. These vegetation series show peculiar sucesional dynamism of their communities depending on their traditional use, environmental factors and biogeographical location. Two new subasociations, Ulici eriocladi-Cistetum ladamferi cistetosum albidi and Phyllireo angustifoliae-Quercetum lusitanicae cytisetosurn tribracteojati, are described in this paper.
Keywords: Andalusia; Quercus suber woods; Spain; vegetation series

Vegetation changes and human action from the Neolithic to the Bronze Age (7000–4000 BP) in Alicante, Spain, based on charcoal analysis - Badal, Ernestina; Bernabeu, Joan; VERNET, J. L. (Vegetation History and Archaeobotany, 1994)
Charcoal analysis reveals various palaeo-eco- logical phases from the Neolithic to the Bronze Age. Ag- riculture starts about 7000 B.P. in favourable ecological conditions. Most of the charcoal spectra from sites iin the coast represent thermomediterranean holm-oak forest; those from the inland mountains represent mesome- diterranean holm-oak forest. The Neolithic I Impressed Ware people were the first to clear the forest to plant their crops. This clearance of primary woodland resulted in the development of secondary vegetation of pine woods or scrub. The scrub reached its maximum during the Bell Beaker phase and Bronze Age in the Cova de les Cendres. In the Neolithic II open air sites, the percent- ages of Quercus ilex/coccifera remain high. This may be the result of a different exploitation of the land, or suit- able conditions for the growth and survival of the vegeta- tion.
Keywords: bronze; CHARCOAL ANALYSIS; human impact; Neolithic; Spain

CRECIMIENTO DE LAS POBLACIONES DE INSECTOS DEL GRUPO <;ERAMBYX CERDO EN LA DEHESA ARBOLADA EXTREMEÑA - del Moral de la Vega, J; Casado Ponce, D; Gallego Girón, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This comunication gives the results of a study cat.:fied out on the damages caused by the Cerambyx cerdo beetles on the cork oaks Quercus suber, Quercus rotundifolia, in the oak forest of Estremadura (Southwest Spain), mainly in the Badajoz province. These species were taxonomicaly identified and their population examined in relation to different variable agrosystems. K.W.:
Keywords: Cerambyx cerdo; Estremadura; Quercus; Spain

CRECIMIENTO DE LAS POBLACIONES DE INSECTOS DEL GRUPO <;ERAMBYX CERDO EN LA DEHESA ARBOLADA EXTREMEÑA - del Moral de la Vega, J.; Casado Ponce, D.; Gallego Girón, M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This comunication gives the results of a study cat.:fied out on the damages caused by the Cerambyx cerdo beetles on the cork oaks Quercus suber, Quercus rotundifolia, in the oak forest of Estremadura (Southwest Spain), mainly in the Badajoz province. These species were taxonomicaly identified and their population examined in relation to different variable agrosystems. K.W.:
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Cerambyx cerdo; Estremadura; Quercus; Spain

EL ALCORNOCAL EN ANDALUCIA. COMPORTAMIENTO ECOLOGICO, FITOCENOLOGIA, FENOMORFOLOGIA, REGENERACION POSTFUEGO, USOS Y CONSERVACION - Pérez Latorre, A V; Nieto Caldera, J M; Cabezudo Artero, B (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
We llave carried out a study about Quercus suber forests in Andalusia (Spain). This study was made under the following points of view: ecological behaviour, flora, fitosociology, successional dynamism, vegetal s'cenery, eco-morphology, pheno-morphology, post-fire regeneration, conservation, ethnobotany and biogeography. We have obtained interesting data and conclusions about them. They have been quite summed up in this papero
Keywords: Andalusia; Cork oak forests; Quercus suber; Spain

Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L M; Bautista, L M; Lázaro, E (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork

Geographical variation in the density of the white stork Ciconia ciconia in Spain: Influence of habitat structure and climate - Carrascal, L. M.; Bautista, L. M.; Lázaro, E. (Biological Conservation, 1993)
The spatial variation in the density of white storks Ciconia ciconia in Spain is analysed with respect to landscape and meteorological variables. The density of breeding pairs in 1985 was negatively correlated with surface cover of woodlands and shrublands, and posi- tively correlated with the area of dry or wet grasslands, reflecting .food availability and foraging preferences of the storks. Average minimum temperature in April-May (the first .few days after hatching) was also negatively correlated with stork density, and the reproductive success in a colony at El Tietar (Avila) was inversely correlated with the number of days with precipitation in May. The negative influence of minimum temperature and precipitation on breeding density appears to be linked with the mortality of recently born nestlings. Practical recommendations are made for the conserva- tion of the Spanish population of white storks through incentive use of pastures, meadows and 'dehesas' for cattle grazing. Reintroduction efforts must be direct towards zones having large areas of these habitats, and mild weather
Keywords: climate; distribution; habitat; Spain; white stork

BREEDING ECOLOGY OF THE BLUE TIT PARUS-CAERULEUS IN EASTERN SPAIN - A COMPARISON WITH OTHER LOCALITIES WITH SPECIAL REFERENCE TO CORSICA - GILDELGADO, J A; López, G; BARBA, E (ORNIS SCANDINAVICA, 1992)
Aspects of the breeding ecology of the Blue Tit Parus caeruleus were studied in intermediate stages of succession in a holm oak forest at Monte Poblet (eastern Spain) from 1985 to 1991. In different years the density in two plots without nest-boxes varied between 1.0 and 6.5 pairs per 10 ha. Nestbox introduction seems to have increased the density of breeding pairs. The mean laying date was earlier (6 vs. 13 May) in low altitude (500-750 m a.s.l.) plots than in a high altitude (900-1000) m a.s.l.) plot, but clutch size (6.9 vs. 6.5 eggs) was not significantly different (mean 6.6 eggs). No differences in mean laying dates were found between years. Significant differences in clutch size were found only between two years at the high altitude site. There was a slight, non-significant, seasonal decline in clutch size. No second clutches were laid. These results are discussed in the context of other Mediterranean studies with special focus on the differences and similarities between Corsican and mainland populations. It is shown that most of the characteristics of the Corsican population (i.e. density, habitat use, laying date, clutch size, number of broods per year) are shared by some populations on the mainland. On the other hand, some breeding traits of Blue Tit populations in southern France are closer to those of Central and North European populations than to the Iberian ones.
APS
Keywords: Blue tit; breeding ecology; Holm oak forest; nest-boxes; Parus cearuleus; Spain; succession stages

HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates

HUMAN-PLANT RELATIONSHIPS DURING THE COPPER AND BRONZE AGES IN THE BAZA AND GUADIX BASINS (GRANADA, SPAIN) - ARIZA, M O R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
The anthracological study of six sites in the north of province of Granada (Spain) has uncovered vegetation for the Copper Age formed by a dense oak grove belonging to the association Rhamno-Quercetum cocciferae. In the Bronze Age, the intensification of agriculture caused changes in the vegetation, reflected in the anthracological diagrams by the increase in Pinus halepensis and the decrease of Quercus ilex-coccifera, as well a decline in the woodlands and an expansion of the legumes. The different species present in the vicinity of the site (or in a greater radius), servings such specific functions as the making of tools and utensils, house construction, and firewood for the hearth or for fours, give us preliminary insights into the ways in which these populations used space and their vegetal environment
Keywords: CHARCOAL ANALYSIS; COPPER AGE; Granada; Spain

Recent changes in landscape structure and function in a Mediterranean region of SW Spain (1950–1984) - Ales, R. F.; Martin, Angel; Ortega, Fernando; Ales, E. E. (Landscape Ecology, 1992)
Recent economic development has altered landscape structure and function of a mediterranean region in Southwestern Spain. Intensive agricultural systems have concentrated in the more fertile areas, while margi- nal ones have been abandoned. As a result, landscape structure has changed. Consequences of this structural change on landscape processes are discussed.
Keywords: agroecology; biological conservation; dofiana national park; guadalquivir valley; sierra morena; Spain

SOIL EVOLUTION AFTER FIRE IN QUERCUS-ILEX AND PINUS-HALEPENSIS FORESTS - FERRAN, A.; SERRASOLSAS, I.; Vallejo, V. R. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Four contrasted burned sites in Catalonia (NE Spain) have been compared to-illustrate the diversified response to fire depending on the interaction of substrate-vegetation characteristics. Data from plant cover evolution, forest floor layers and soil chemical properties demonstrated that the garrigue on limestone is the most resilient ecosystem as a result of the resprouting capacity of Ouercus coccifera and the high soil stability. The shrubland on marls was however, the least resilient, with the poorest plant regeneration and greatest erosion rates. The plant communities on conglomerates and the holm oak forest on schists, represented intermediate situations, where the variable degree of erosion and nutrient losses were compensated by a rapid plant colonization just after the fire.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: burned sites; ecosystem resilience; fire; Quercus coccifera; Quercus ilex; Shrubland; Spain

STRUCTURE OF MIXED HOLM-OAK (QUERCUS-ILEX) ALEPPO PINE (PINUS-HALEPENSIS) FORESTS IN NORTHEASTERN SPAIN - Espelta, J. M.; GENE, C.; Retana, J.; TERRADAS, J. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Mixed forests of Aleppo pine (Pinus halepensis) and holm-oak (Quercus ilex) cover a great part of Northeastern Spain. Nevertheless, little is known about their structure, dynamics and regeneration. For some years, a research group in CREAF has collected data about those aspects, in order to use them to develop models that could be used as a tool for forest management. Previous results obteined about the structure of these stands are presented in the present paper.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: mixed forests; Pinus halepensis; Quercus ilex; Spain

ABUNDANCE AND FOOD-SEARCHING INTENSITY OF WOOD MICE (APODEMUS-SYLVATICUS) IN FRAGMENTED FORESTS - Tellería, J L; Santos, T; ALCANTARA, M (JOURNAL OF MAMMALOGY, 1991)
Abundance, food-searching intensity, physiological status, and population attributes of wood mice (Apodemus sylvaticus) were studied in forest islands of central Spain. Seventeen isolated woodlots (Quercus rotundifolia) ranging from 0.1 to 280 ha were studied. The results show high densities of mice and high rates of predation on acorns in the smaller forests.
Keywords: acorns predation; Apodemus sylvaticus; forest islands; Quercus rotundifolia; Spain; wood mice

WINTER DIET OF RED DEER STAG (CERVUS-ELAPHUS L) AND ITS RELATIONSHIP TO MORPHOLOGY AND HABITAT IN CENTRAL SPAIN - ALVAREZ, G; MARTINEZ, T; MARTINEZ, E (FOLIA ZOOLOGICA, 1991)
The winter diet of red deer stags in a mediterranean environment of Central Spain is studied. Tree foliage and shrubs made up 95.5% of the diet, particularly Quercus rotundifolia (35.4%). Arbutus unedo (19.7%), Rosmarinus officinalis (9.4%), Phillyrea angustifolia (7%), Erica spp. and Cistus ladanifer. Herbaceous species formed 4% of the diet, mainly in a dry condition. There was a high similarity between the diets in the two periods studied, December and the end of January, with greater diversity in December. In January, the dominance of Quercus rotundifolia and Arbutus unedo increased. A relationship was detected of diet with body weight and antler growth. The largest animals consumed Arbutus unedo heavily, indicating a preference for forest understories with dense developed shrubs in mountain areas, while the smaller individuals associated with Erica umbellata, Phillyrea angustifolia and herbaceous species, had a wider diet niche and occupied less sheltered zones.
APS
Keywords: diet; Mediterranean; red deer; Spain

Datos sobre la vegetación silicícola de Andalucia I. - Caldera, J M Nieto; Latorre, A V Pérez; Cabezudo, B (Acta botánica malacitana, 1990)
: The phytocenologic study about climatophilous vegetation series, which inhibat on siliceous soils in Málaga, Cádiz, Sevilla and Granada (Spain), has produced the identification of six vegetation series. It is described the following new syntaxa: Smilaco mauritanicae-Quercetum rotundifOliae quercetosum suberis,Teucrio baetici-Querceturn suberis quercetosum rotundifoliae and Cytiso baetici-Arbutetum unedonis.
Keywords: Cádiz; Cork oak forests; Granada; holm oak forests; Málaga; phytosociology; Sevilla; siliceous soils; Spain; strawbwerry tree copses; vegetation series

THE TIMING OF BREEDING AND CLUTCH SIZE OF BLUE TITS (PARUS-CAERULEUS) IN AN EVERGREEN HOLM OAK HABITAT IN SOUTHERN SPAIN - ISENMANN, P; ALES, E; MORENO, O (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1990)
APS
Keywords: blur tits; clutch size; Holm oak; Parus cearuleus; Spain

Caractérisation de formations végétales mediterranéennes à partir de données ‘Thematic Mapper’ Une étude de cas en Andalousie (Espagne) - LACAZE, BERNARD; Joffre, Richard (International Journal of Remote Sensing, 1987)
Abstract The study is focused on the characterization of vegetation formations in a Mediterranean area (943 km2) located in southern Spain: herbaceous canopies (rangelands), shrubby vegetation (?matorral?) and complex woody/herbaceous formations (?dehesa?). Vegetation formations (physiognomical units) have been characterized by their spectral responses in the six reflective TM channels and by vegetation indices. From the ratio index TM4/TM3 there has been derived a map displaying seven classes (water, bare soil and five biomass levels reflecting the hierarchy of vegetation formations). Channels TM3, TM4 and TM5 have been considered for a supervised classification into nine land-cover categories (seven vegetation formations, bare soil and water). The proportion of correct classification of vegetation formations is about 78 per cent when considering test areas. Classification made from three principal components gives similar results.
doi: 10.1080/01431168708954777
Keywords: Automatic classification; biomass; characterization; Europe (citation); Image interpretation; land use; Mediterranean vegetation; Multispectral remote sensing; rangeland; Regional study; Satellite observation; Shrubbery; Spain; Survey; Thematic map; Vegetation type